2023
DOI: 10.1002/smll.202302587
|View full text |Cite
|
Sign up to set email alerts
|

An Immunomodulatory Biomimetic Single‐Atomic Nanozyme for Biofilm Wound Healing Management

Abstract: Nanozyme‐driven catalytic antibacterial therapy has become a promising modality for bacterial biofilm infections. However, current catalytic therapy of biofilm wounds is severely limited by insufficient catalytic efficiency, excessive inflammation, and deep tissue infection. Drawing from the homing mechanism of natural macrophages, herein, a hollow mesoporous biomimetic single‐atomic nanozyme (SAN) is fabricated to actively target inflamed parts, suppress inflammatory factors, and eliminate deeply organized ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The biofilm-induced inflammatory response exacerbates persistent infections and delays chronic wound healing. Therefore, the capacity to puncture and destroy biofilms is a significant indicator of the chronic wound-healing potential of antimicrobial agents. The specific treatments of S. aureus biofilms were consistent with the six groups described above.…”
Section: Resultssupporting
confidence: 65%
“…The biofilm-induced inflammatory response exacerbates persistent infections and delays chronic wound healing. Therefore, the capacity to puncture and destroy biofilms is a significant indicator of the chronic wound-healing potential of antimicrobial agents. The specific treatments of S. aureus biofilms were consistent with the six groups described above.…”
Section: Resultssupporting
confidence: 65%
“…In vivo experiments revealed that FePN SAzyme treatment of wounds stimulated by exogenous nearinfrared (NIR) irradiation significantly reduced inflammatory cell infiltration and promoted epidermal regeneration, suggesting a synergistic therapeutic wound-healing effect of outstanding POD-mimic capacity-assisted CDT effect and localized photothermal efficacy. Similarly, Xu et al [107] also reported a Mn single-atom nanozymes for catalytic/photothermal treatment of bacteria-infected wound. The Mn single-atom nanozymes possessed NIR photothermal-induced enhanced POD-mimetic activity, which could catalyze the •OH-generation in the presence of H 2 O 2 .…”
Section: Wound Healingmentioning
confidence: 92%
“…Inspired by this strategy, Zhang et al encapsulated IL-4 (a cytokine) within single-atom Co nanozymes (Co@SAHS) and then coated it with the RAW 264.7 cell membrane (RCM) to form Co@SAHSs@IL-4@RCM. 60 The RCM leverages its specific proteins to home inflammation site, helping Co@SAHSs@IL-4@RCM accumulation at the infection site. Subsequently, under the action of the nanozyme's POD-like catalytic effect, ˙OH is produced to kill bacteria and disrupt the RCM, releasing IL-4 and thus modulating macrophages towards an M2 phenotype to alleviate the inflammatory response (Fig.…”
Section: Improvement Of the Antimicrobial Capacity Of Pod Nanozymesmentioning
confidence: 99%